Rural credit follow-up survey1956-7: general review report - Reserve Bank of India. Economic Department (Bombay : Reserve Bank of India, 1960)
This book is the report of the annual investigation conducted by the Reserve Bank of India on India rural credit survey for the period 1956-7. It is prepared by the Economic Department and the Department of Statistics of the Bank.
usc 19/02/2019
Loans
Keywords: Agricultural credit; Rural conditions; India